The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0128885
|View full text |Cite
|
Sign up to set email alerts
|

Basketball Shot Types and Shot Success in Different Levels of Competitive Basketball

Abstract: The purpose of our research was to investigate the relative frequencies of different types of basketball shots (above head, hook shot, layup, dunk, tip-in), some details about their technical execution (one-legged, two-legged, drive, cut, …), and shot success in different levels of basketball competitions. We analysed video footage and categorized 5024 basketball shots from 40 basketball games and 5 different levels of competitive basketball (National Basketball Association (NBA), Euroleague, Slovenian 1st Div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 9 publications
5
66
0
9
Order By: Relevance
“…Although a discriminant analysis of game-related statistics has been an established method and widely performed in basketball research, it is not enough to fully investigate the game. On the other hand, several recent studies have focused on specific elements of the game such as shot (22), screen (23)(24)(25), fast break (26), substitution (27) and foul (28,29). Conducting those types of studies would compensate the limitation and help to fully understand the characteristics of the game.…”
Section: Discussionmentioning
confidence: 99%
“…Although a discriminant analysis of game-related statistics has been an established method and widely performed in basketball research, it is not enough to fully investigate the game. On the other hand, several recent studies have focused on specific elements of the game such as shot (22), screen (23)(24)(25), fast break (26), substitution (27) and foul (28,29). Conducting those types of studies would compensate the limitation and help to fully understand the characteristics of the game.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, NBA players are characterized by a superior strength, jump conditions (Gonzalez, et al, 2013;Sampaio, Lago, & Drinkwater, 2010) and a strong role specialization . Then, it seems logical to promote predefined and coordinated outside-inside behaviours like cutting towards the basket for an alley-oop, since players' physical condition allows them to easily score through dunking (Erčulj & Štrumbelj, 2015). More importantly, our findings point out the importance of specific inside players' displacement without the ball to increase odds of receiving the ball in optimal conditions as close to the basket as possible, enhancing scoring options.…”
Section: Offensive Performancementioning
confidence: 76%
“…In the NBA, there is a greater use of the inside pass compared to the European teams (Mavridis, Tsamourtzis, Karipidis, & Laios, 2009). In basketball, the majority of possessions are solved in the inside, chiefly in the NBA due to the athletic complexion of centers, making them specialists in shooting near the basket and dunking with a higher rate of effectiveness (Erčulj & Štrumbelj, 2015). Previous research exploring NBA playoffs series reported greater effectiveness in ball possessions when using inside pass (Courel-Ibáñez, McRobert, Ortega Toro, & Cárdenas Vélez, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ball possessions recorded had a score difference below 10 points (average = 1.64 ± 4.69 points). The choice of this specific sample was deliberate; first, NBA is the most important basketball club competition of the world; second, Playoffs confronted best season teams to become the champion, thus the maximum competitive level was expected until the end of the game; and third, possessions with short score differences ensure high players' activation and concentration levels (Erčulj & Štrumbelj, 2015).…”
Section: Samplementioning
confidence: 99%